Long waited brothers or unwelcome guests: the logic of reception mechanisms of a receiving state: Turkey and its asylum seekers in 1989 and 1991 - Çatır, Gül. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This thesis scrutinizes the impact of the nation-state in shaping the immigration and asylum flows. It sees the state as the primary agent in determining the reception contexts that await the immigrants, asylum seekers and refugees in a host state. Furthermore, the reception conditions come into being as a result of the interplay between foreign policy, domestic politics, and ethno-national considerations of the receiving state. It argues that the explanation of immigration and asylum practices of the nation-state by reserving the greatest weight to identity politics remains incomplete. That is, the reception contexts of the nation-state in each population flow are an outcome of various dynamics. Hence the reception contexts should be addressed individually in each and every immigration and asylum case. It follows that the ethnic national, liberal national and cosmopolitan premises, as ideal type constructs denoting partiality and impartiality of the state practices vis-à-vis the immigrant and refugee groups, could be encountered in state practices and discourses, yet they would not be dominating because of the interaction between the foreign policy, domestic politics and ethnic considerations. This study tries to demonstrate this argument by using two case studies of mass influx of refugees, one from Bulgaria in 1989 and the other from Iraq in 1991, in the reception setting of Turkey, which is generally regarded as governed by an overemphasis on ethnicity and identity when it comes to its immigration and asylum policies. In this regard, this thesis maintains that the case studies, selected on the basis of ethnic differentiation of the newcomers, reflected the reception practices of the Turkish state as a resultant of foreign and domestic politics as well as ethnicity considerations.
Keywords: Asylum, Right of -- Turkey.; Emigration and immigration -- Turkey.; Refugees -- Turkey.